2010
DOI: 10.1590/s0073-47212010000400018
|View full text |Cite
|
Sign up to set email alerts
|

Endemism analysis of Neotropical Pentatomidae (Hemiptera, Heteroptera)

Abstract: ABSTRACT. The definition of areas of endemism is central to studies of historical biogeography, and their interrelationships are fundamental questions. Consistent hypotheses for the evolution of Pentatomidae in the Neotropical region depend on the accuracy of the units employed in the analyses, which in the case of studies of historical biogeography, may be areas of endemism. In this study, the distribution patterns of 222 species, belonging to 14 Pentatomidae (Hemiptera) genera, predominantly neotropical, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
(50 reference statements)
1
18
2
Order By: Relevance
“…Ferrari et al. (), for example, showed that no area was delimited in poorly sampled regions of their data, which was different from our findings. On the other hand, critics might argue that a well‐sampled region with uniformly distributed points could complete a pattern of gradual substitution, for example, resulting in fewer areas.…”
Section: Discussioncontrasting
confidence: 99%
“…Ferrari et al. (), for example, showed that no area was delimited in poorly sampled regions of their data, which was different from our findings. On the other hand, critics might argue that a well‐sampled region with uniformly distributed points could complete a pattern of gradual substitution, for example, resulting in fewer areas.…”
Section: Discussioncontrasting
confidence: 99%
“…The higher the number of endemic species in the area and the higher the endemicity of those species, the more likely it is for a group of cells to be considered an "area of endemism" (Szumik & Goloboff 2004). Nowadays, this programme is widely used (Ferrari et al 2010;Mendoza-Fernández et al 2014). The information was obtained from 10×10 km grid cells.…”
Section: Biogeographical Analysismentioning
confidence: 99%
“…Studies using arthropod data for the definition of AEs in the AF and/or Neotropical region usually focus on few taxa (Sigrist & Carvalho, 2008) and/or in very specific taxa (Lowenberg-Neto & Carvalho, 2009;Ferrari et al, 2010;DaSilva et al, 2015;Oliveira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%